Pug's new puppy ebook - May, Kyla (Diary of a Pug, 2023)
An eighth Branches early chapter book featuring everyone's favorite pug, Bub, and his human, Bella! Pick a book. Grow a Reader! This series is part of Scholastic's early chapter book line, Branches, aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, thesebooks will boost reading confidence and stamina. ​​​​​​​Branches books help readers grow! ​​​​​​​ ​​​​​​​Bub the pug and his human, Bella, are taking care of Nana's new puppy, Harlow. They can't wait to teach Harlow some new tricks! But training a puppy isn't an easy job. Will they be able to teach Harlow anything before Nana comes home? ​​​​​​​ ​​​​​​​With full-color artwork throughout, this funny and charming diary-format early chapter book is perfect for anyone who believes a furry pal is the best kind of friend.